2021
DOI: 10.3390/ma14112951
|View full text |Cite
|
Sign up to set email alerts
|

Computer Analysis of the Effect of Activation Temperature on the Microporous Structure Development of Activated Carbon Derived from Common Polypody

Abstract: This paper presents the results of a computer analysis of the effect of activation process temperature on the development of the microporous structure of activated carbon derived from the leaves of common polypody (Polypodium vulgare) via chemical activation with phosphoric acid (H3PO4) at activation temperatures of 700, 800, and 900 °C. An unconventional approach to porous structure analysis, using the new numerical clustering-based adsorption analysis (LBET) method together with the implemented unique gas st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Therefore, the concept of carrying out a new original series of analyses using more advanced and reliable methods of porous structure analysis, i.e., QSDFT [42][43][44][45] and the LBET [46][47][48][49][50] methods, taking into account, among other things, surface heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the concept of carrying out a new original series of analyses using more advanced and reliable methods of porous structure analysis, i.e., QSDFT [42][43][44][45] and the LBET [46][47][48][49][50] methods, taking into account, among other things, surface heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…In the present research, the following parameters and indicators were determined: the specific surface area S QSDFT [m 2 g −1 ], the volume of micropores V QSDFT [cm 3 g −1 ], and the pore size distribution PSD obtained via the QSDFT method [42][43][44][45], the value of parameters of the porous structure. i.e., the volume of the first adsorbed layer V hA [cm 3 g −1 ], the dimensionless energy parameter for the first adsorbed layer Q A /RT, the dimensionless energy parameter for the higher adsorbed layers, B C , the geometrical parameter of the porous structure determining the height of the adsorbate molecule clusters α, the geometrical parameter of the porous structure determining the width of the adsorbate molecule clusters β calculated via the LBET method [46][47][48][49][50]. Additionally, via the fast numerical multivariate identification procedure of adsorption systems, the following information were determined: the value of the surface heterogeneity parameter h, the value of the dispersion of fitting errors σ e , the value of the indices of identification reliability w id and the adsorption energy distributions AED on the first adsorbed layer, obtained for all analyzed activated carbons.…”
Section: Methodsmentioning
confidence: 99%
“…According to the Bruner, Emmett, and Teller (BET) method [15], the specific surface area of (AC) was computed. The Dubinin-Radushkevich (DR) equation [16] was used to calculate the microspore volume. The nitrogen pore volume was obtained from the maximum relative pressure (P/Po=0.99) [17].…”
Section: N2 Adsorption-desorption Isothermsmentioning
confidence: 99%
“…Physical activation includes the oxidation and gasification of char at high temperatures. In the process of chemical activation, carbonization and activation are performed in one stage by thermal decomposition of raw materials impregnated with some chemicals, such as ZnCl 2 , NaOH, KOH, K 2 CO 3 , and H 3 PO 4 . When activated, the textural characteristics of the materials may also change. It was shown that the sorption capacity of materials increases as a result of the activation process .…”
Section: Introductionmentioning
confidence: 99%